Clinical, radiological and functional outcome in unstable intertrochanteric fracture : comparison between dynamic hip screw (DHS) and intramedullary devices - Muhammad Faiz Hang Md Kashap (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
An observational cohort study of 100 patients with unstable intertrochanteric fractures who had been treated either with Dynamic Hip Screw (DHS) or intramedullary device in Hospital Serdang, Selangor and Hospital Tengku Ampuan Afzan, Kuantan, Pahang from November 2016 till June 2018. This research aimed to compare clinical, radiological and functional outcomes post-operative fixation of using Dynamic Hip Screw (DHS) with those of patients who had been treated with the intramedullary device in unstable intertrochanteric fracture.The clinical outcome parameter includes the time of operation, amount of blood loss, require transfusion and surgical site infection. Tips-apex distance and neck-shaft angle were also evaluated, and follow-up was undertaken for 1 year. Any changes in the value were recorded. They were evaluated for functional outcomes with Harris Hip Scores at 1 year post-operatively. 47 patients had undergone the Dynamic Hip Screw (DHS) technique and another 51 patients who had been subjected to Intramedullary Devices technique. Mean age was 68 years old. The predominant mechanism of injury for all patients was a slippery floor with 87.2% prevalence. The mean operative time was significantly less in Intramedullary devices than in the DHS group. 7 patients in the DHS group had cut-out screw while none experienced in the intramedullary group. There was no significant association between the need for transfusion or surgical site infection in both groups. However, in DHS group percentage need for transfusion is higher about 55.6%. The functional evaluation using the Harris score after one year showed, there was no significant difference between both groups. As a conclusion, intramedullary devices technique was found to be superior to DHS in term of the duration of surgery, intraoperative blood loss, and screw cut-out complication in treating the unstable intertrochanteric fracture, whereas both techniques possess the same risk of functional outcome and other complication.